Opportunities for Helicobacter pylori Eradication beyond Conventional Antibiotics - Camilia Metadea Aji Savitri; Kartika Afrida Fauzia; Ricky Indra Alfaray; Hafeza Aftab; Ari Fahrial Syam; Masrul Lubis; Yoshio Yamaoka; Muhammad Miftahussurur (Microorganisms)
Helicobacter pylori (H. pylori) is a bacterium known to be associated with a significant risk of gastric cancer in addition to chronic gastritis, peptic ulcer, and MALT lymphoma. Although only a small percentage of patients infected with H. pylori develop gastric cancer, Gastric cancer causes more than 750,000 deaths worldwide, with 90% of cases being caused by H. pylori. The eradication of this bacterium rests on multiple drug regimens as guided by various consensus. However, the efficacy of empirical therapy is decreasing due to antimicrobial resistance. In addition, biofilm formation complicates eradication. As the search for new antibiotics lags behind the bacterium’s ability to mutate, studies have been directed toward finding new anti-H. pylori agents while also optimizing current drug functions. Targeting biofilm, repurposing outer membrane vesicles that were initially a virulence factor of the bacteria, phage therapy, probiotics, and the construction of nanoparticles might be able to complement or even be alternatives for H. pylori treatment. This review aims to present reports on various compounds, either new or combined with current antibiotics, and their pathways to counteract H. pylori resistance.